Upconversion nanoparticles, polymer composite including the same and method for manufacturing the same

KR103030936B1Active Publication Date: 2026-10-13KOREA INST OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020240165207
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2026-10-13
Estimated Expiration
2044-11-19

Smart Images

  • Figure 112024127191113-PAT00001_ABST
    Figure 112024127191113-PAT00001_ABST
Patent Text Reader

Abstract

The upconversion nanoparticle is formed in a core / quadruple-shell structure comprising: a core that absorbs infrared radiation of a first wavelength and emits blue light; a crystalline intermediate layer formed around the core; an emitting layer formed around the intermediate layer that absorbs infrared radiation of a second wavelength and emits red light, and emits green light through infrared radiation of a third wavelength that is absorbed or transmitted; an energy transfer layer formed around the emitting layer that transmits absorbed infrared radiation of a third wavelength to the emitting layer; and an absorption layer formed around the energy transfer layer that absorbs infrared radiation of a third wavelength and transmits it to the emitting layer through the energy transfer layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to upconversion nanoparticles, polymer composites containing the same, and a method for manufacturing them. More specifically, it relates to a polymer composite manufactured using a polymer and an upconversion nanofluorophor that exhibits blue / red / green light emission. Background Technology

[0003] 3D display technology focuses on providing users with a sense of immersion and depth through next-generation display technologies such as Virtual Reality (VR), Augmented Reality (AR), and holograms. Among these, volumetric displays are implemented in various ways to allow users to directly experience the depth and three-dimensionality of the screen. However, existing holographic displays or glass-based stereoscopic display methods have limitations in terms of practicality due to restricted viewing angles and complex implementation methods when realizing such volumetric images.

[0004] To overcome this, a technology has been proposed to implement a volumetric display by stacking multiple light-emitting layers. Although this method constructs a display by stacking layers that emit blue, red, and green light respectively, it has the disadvantage of being structurally very complex and requiring a complicated manufacturing process.

[0005] To solve this problem, a method for fabricating a light source by mixing R / G / B multicolor light-emitting nanoparticles into a polymer composite has been introduced, but the synthesis process of nanoparticles capable of full-color light emission is known to be complex and time-consuming. For full-color light emission, multiple layers of multi-shells must be formed around the nanoparticle core, and there was a limitation in that as the number of shells increased, the synthesis of the nanoparticles became difficult and the light emission intensity could weaken.

[0006] In Non-Patent Literature 1 of the prior art literature, various colors including red, green, and blue were realized through three near-infrared wavelengths using up-conversion nanoparticles with a hexagonal core / seven-shell structure. In this study, a total of seven shells had to be formed to realize red, green, and blue luminescence, which resulted in the disadvantage of making the nanoparticle structure very complex and increasing the synthesis time.

[0007] The study in Non-Patent Literature 2 of the prior art literature was a study on hexagonal core / quadrishell nanoparticles that achieved various emission colors by controlling the wavelength and pulse of a laser. Although this study was applied to the field of transparent displays, there was a problem in that the emission intensity weakened during the process of controlling the pulse. This made it difficult to achieve all three colors (red / green / blue) while maintaining strong emission intensity.

[0008] In addition, Patent Document 1 of the prior art introduced a technology regarding an upconversion nanophosphor that achieves red / green / blue luminescence using tetragonal core / hexashell nanoparticles. However, this nanoparticle also had the limitation that a large number of shells had to be formed around the core.

[0009] As such, existing technologies have achieved red, green, and blue luminescence through multi-shell structures, but nanoparticle synthesis is complex and time-consuming, and there were limitations in luminescence intensity. Prior art literature

[0011] (Patent Document 0001) KR 10-2448424 B1

[0012] Near-infrared manipulation of multiple neuronal populations via trichromatic upconversion (Nature communications, F. Zhang et al, 2021, 12, 5662)Temporal fullcolor tuning through nonsteady-state upconversion (Nature Nanotechnology, R. Deng et al. 2015, 10, 237) The problem to be solved

[0013] Accordingly, the technical problem of the present invention is conceived from this point, and the objective of the present invention is to provide upconversion nanoparticles that have excellent red / green / blue luminescence intensity while reducing the number of shells.

[0014] Another objective of the present invention is to provide a polymer composite comprising the upconversion nanoparticles.

[0015] Another objective of the present invention is to provide a method for manufacturing the upconversion nanoparticles. means of solving the problem

[0017] An upconversion nanoparticle according to one embodiment for realizing the above-described objective of the present invention is formed with a core / quadruple-shell structure represented by the following chemical formula 1, comprising: a core that absorbs infrared rays of a first wavelength and emits blue light; a crystalline intermediate layer formed around the core; an emitting layer formed around the intermediate layer that absorbs infrared rays of a second wavelength and emits red light, and emits green light through infrared rays of a third wavelength that are absorbed or received; an energy transfer layer formed around the emitting layer and transfers absorbed infrared rays of a third wavelength to the emitting layer; and an absorption layer formed around the energy transfer layer that absorbs infrared rays of a third wavelength and transfers them to the emitting layer through the energy transfer layer.

[0018] [Chemical Formula 1]

[0019] NaGd1-a-b-c L c F4:Yb 3+ a ,Tm 3+ b / NaY 1-d M d F4 / NaEr 1-e-f-g Q e F4:Yb 3+ f ,Tm 3+ g / NaY 1-h-i R h F4:Yb 3+ i / NaNd 1-j-k T j F4:Yb 3+ k

[0020] Here, a is a real number such that 0 < a ≤ 1, b is a real number such that 0 < b ≤ 0.5, c is a real number such that 0 ≤ c ≤ 1, and c can be selected within the range satisfying the condition 0 < a + b + c ≤ 1, d is a real number such that 0 ≤ d ≤ 1, e is a real number such that 0 ≤ e < 1, f is a real number such that 0 ≤ f < 1, g is a real number such that 0 ≤ g ≤ 0.5, and e can be selected within the range satisfying the condition 0 ≤ e + f + g < 1, h is a real number such that 0 ≤ h ≤ 1, i is a real number such that 0 ≤ i ≤ 1, where h is any one selected within the range satisfying 0 ≤ h + i ≤ 1, j is a real number such that 0 ≤ j < 1, and k is a real number such that 0 ≤ k < 1, where j is 0 It can be selected within the range satisfying the condition ≤ j + k < 1, and L, M, Q, R and T are any one selected from the group consisting of rare earth elements and combinations thereof.

[0021] In an embodiment of the present invention, L is any one selected from the group consisting of rare earth elements and combinations thereof, and the rare earth element in L is any one selected from the group consisting of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Tb, Dy, Ho, Er, and Lu; M is any one selected from the group consisting of rare earth elements and combinations thereof, and the rare earth element in M ​​is any one selected from the group consisting of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; Q is any one selected from the group consisting of rare earth elements and combinations thereof, and the rare earth element in Q is any one selected from the group consisting of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, and Lu; and R is any one selected from the group consisting of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Lu, and combinations thereof. There is one, and T is any one selected from the group consisting of rare earth elements and combinations thereof, and in T, the rare earth element may be any one selected from the group consisting of Y, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, and Lu.

[0022] In an embodiment of the present invention, the first wavelength may be 980 ± 50 nm, the second wavelength may be 1532 ± 50 nm, and the third wavelength may be 800 ± 50 nm.

[0023] In an embodiment of the present invention, the upconversion nanoparticle may have a single hexagonal crystal phase.

[0024] In an embodiment of the present invention, white or various colors can be emitted depending on the relative intensity of the applied 980 ± 50 nm, 800 ± 50 nm, and 1532 ± 50 nm near-infrared rays.

[0025] A polymer composite according to one embodiment for realizing another objective of the present invention described above comprises the upconversion nanoparticles.

[0026] A method for manufacturing upconversion nanoparticles according to one embodiment for realizing another objective of the present invention described above is NaGd 1-a-b-c L c F4:Yb 3+ a ,Tm 3+ b A step of forming a nano-sized core represented by the chemical formula; NaY around the core 1-d M d A step of forming a first shell represented by the chemical formula of F4; NaEr around the first shell 1-e-f-g Q e F4:Yb 3+ f ,Tm 3+ g A step of forming a second shell represented by the chemical formula of; NaY around the second shell 1-h-i R h F4:Yb 3+ i A step of forming a third shell represented by the chemical formula of; and NaNd around the third shell 1-j-k T j F4:Yb 3+ k The method includes the step of forming a fourth shell represented by the chemical formula of; and

[0027] Here, a is a real number such that 0 < a ≤ 1, b is a real number such that 0 < b ≤ 0.5, c is a real number such that 0 ≤ c ≤ 1, and c can be selected within the range satisfying the condition 0 < a + b + c ≤ 1, d is a real number such that 0 ≤ d ≤ 1, e is a real number such that 0 ≤ e < 1, f is a real number such that 0 ≤ f < 1, g is a real number such that 0 ≤ g ≤ 0.5, and e can be selected within the range satisfying the condition 0 ≤ e + f + g < 1, h is a real number such that 0 ≤ h ≤ 1, i is a real number such that 0 ≤ i ≤ 1, where h is any one selected within the range satisfying 0 ≤ h + i ≤ 1, j is a real number such that 0 ≤ j < 1, and k is a real number such that 0 ≤ k < 1, where j is 0 It can be selected within the range satisfying the condition ≤ j + k < 1, and L, M, Q, R and T are any one selected from the group consisting of rare earth elements and combinations thereof.

[0028] In an embodiment of the present invention, L is any one selected from the group consisting of rare earth elements and combinations thereof, and the rare earth element in L is any one selected from the group consisting of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Tb, Dy, Ho, Er, and Lu; M is any one selected from the group consisting of rare earth elements and combinations thereof, and the rare earth element in M ​​is any one selected from the group consisting of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; Q is any one selected from the group consisting of rare earth elements and combinations thereof, and the rare earth element in Q is any one selected from the group consisting of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, and Lu; and R is any one selected from the group consisting of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Lu, and combinations thereof. There is one, and T is any one selected from the group consisting of rare earth elements and combinations thereof, and in T, the rare earth element may be any one selected from the group consisting of Y, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, and Lu.

[0029] In an embodiment of the present invention, the core absorbs infrared rays of a first wavelength and emits blue light, the second shell absorbs infrared rays of a second wavelength and emits red light, and can emit green light through infrared rays of a third wavelength that are absorbed from the fourth shell and transmitted through the third shell.

[0030] In an embodiment of the present invention, the first wavelength may be 980 ± 50 nm, the second wavelength may be 1532 ± 50 nm, and the third wavelength may be 800 ± 50 nm.

[0031] In an embodiment of the present invention, the step of forming a core may include: preparing a first lanthanide complex using dolinium chloride hydrate (GdCl3·6H2O), ytterbium chloride hydrate (YbCl3·6H2O), and thulium chloride hydrate (TmCl3·6H2O); preparing a first methanol solution containing sodium hydroxide (NaOH) and ammonium fluoride (NH4F); and mixing the first methanol solution and the first lanthanide complex to prepare a nanoparticle solution having a core structure.

[0032] In an embodiment of the present invention, the step of forming a first shell may include: a step of preparing a second lanthanide complex using yttrium chloride hydrate (YCl3·6H2O); a step of preparing a first mixed solution by mixing the second lanthanide complex and a core-structured nanoparticle solution; a step of preparing a second methanol solution containing sodium hydroxide (NaOH) and ammonium fluoride (NH4F); and a step of preparing a core / shell structured nanoparticle solution by mixing the second methanol solution and the first mixed solution.

[0033] In an embodiment of the present invention, the step of forming a second shell may include: a step of preparing a third lanthanide complex using erbium chloride hydrate (ErCl3·6H2O), ytterbium chloride hydrate (YbCl3·6H2O), and thulium chloride hydrate (TmCl3·6H2O); a step of preparing a second mixed solution by mixing the third lanthanide complex and a core / shell structured nanoparticle solution; a step of preparing a third methanol solution containing sodium hydroxide (NaOH) and ammonium fluoride (NH4F); and a step of preparing a core / shell / shell structured nanoparticle solution by mixing the third methanol solution and the second mixed solution.

[0034] In an embodiment of the present invention, the step of forming a third shell may include: a step of preparing a fourth lanthanide complex using yttrium chloride hydrate (YCl3·6H2O) and ytterbium chloride hydrate (YbCl3·6H2O); a step of preparing a third mixed solution by mixing the fourth lanthanide complex and a nanoparticle solution having a core / shell / shell structure; a step of preparing a fourth methanol solution containing sodium hydroxide (NaOH) and ammonium fluoride (NH4F); and a step of preparing a nanoparticle solution having a core / shell / shell / shell structure by mixing the fourth methanol solution and the third mixed solution.

[0035] In an embodiment of the present invention, the step of forming a fourth shell may include: preparing a fifth lanthanide complex using neodymium chloride hydrate (NdCl3·6H2O) and ytterbium chloride hydrate (YbCl3·6H2O); preparing a fourth mixed solution by mixing the fifth lanthanide complex with a nanoparticle solution having a core / shell / shell / shell structure; preparing a fifth methanol solution containing sodium hydroxide (NaOH) and ammonium fluoride (NH4F); and preparing a nanoparticle solution having a core / shell / shell / shell / shell structure by mixing the fifth methanol solution with the fourth mixed solution.

[0036] In an embodiment of the present invention, each step may include a step of heat treating at a temperature of 200°C to 370°C for 10 minutes to 4 hours in an inert gas atmosphere. Effects of the invention

[0038] These upconversion nanoparticles and polymer composites containing them significantly simplify the synthesis process by using core / quadruple-shell nanoparticles instead of complex structures such as core / hexa-shell or core / seven-shell. This shortens the nanoparticle manufacturing time, improves productivity, and reduces manufacturing costs.

[0039] Furthermore, nanoparticles with a core / quadruple-shell structure exhibit superior intensity of red, green, and blue luminescence despite having fewer shells than existing prior art. By reducing the number of shells, the conventional drawback of reduced luminescence intensity is overcome, enabling vivid full-color luminescence with high color purity.

[0040] Furthermore, the present invention enables red, green, and blue light emission by adjusting only the wavelength of the laser without the need for conventional pulse control methods. This prevents the problem of reduced light emission intensity and allows for color control in a simpler and more stable manner. Brief explanation of the drawing

[0042] FIG. 1 is a conceptual diagram showing the structure of an upconversion nanoparticle having a core / shell / shell / shell / shell structure, which is an embodiment of the present invention. Figure 2 is a transmission electron microscope image of a core that absorbs infrared rays of 980 nm wavelength and emits blue light, which is Example 1 of the present invention. Figure 3 is a transmission electron microscope image of a core / shell structured upconversion nanoparticle, which is Example 2 of the present invention. Figure 4 is a transmission electron microscope image of a core / shell / shell structured upconversion nanoparticle, which is Example 3 of the present invention. Figure 5 is a transmission electron microscope image of an upconversion nanoparticle with a core / shell / shell / shell structure, which is Example 4 of the present invention. Figure 6 is a transmission electron microscope image of an upconversion nanoparticle with a core / shell / shell / shell / shell structure, which is Example 5 of the present invention. Figure 7 shows the X-ray diffraction patterns of up-conversion nanoparticles according to Examples 1 to 5 of the present invention. Figure 8 shows the emission spectrum when core / shell / shell / shell / shell upconversion nanoparticles according to Example 5 of the present invention are excited by 980 nm infrared light. Figure 9 shows the emission spectrum when core / shell / shell / shell / shell upconversion nanoparticles according to Example 5 of the present invention are excited by 800 nm infrared light. Figure 10 shows the emission spectrum of core / shell / shell / shell / shell upconversion nanoparticles according to Example 5 of the present invention when excited by 1532 nm infrared light. Figure 11 shows a luminescence photograph of a core / shell / shell / shell / shell upconversion nanoparticle solution according to Example 5 of the present invention. FIG. 12 is a color coordinate under conditions in which upconversion nanoparticles of a core / shell / shell / shell / shell structure according to preferred embodiment 5 of the present invention are excited by infrared rays of various wavelengths. Figure 13 shows a photograph of a core / quadruple-shell upconversion nanoparticle-polymer composite according to Example 6 of the present invention. Figure 14 shows a luminescence photograph when an infrared laser is applied to a core / quadruple-shell upconversion nanoparticle-polymer composite according to Example 6 of the present invention. Specific details for implementing the invention

[0043] The following detailed description of the invention refers to the accompanying drawings, which illustrate specific embodiments in which the invention may be practiced. These embodiments are described in sufficient detail to enable those skilled in the art to practice the invention. It should be understood that various embodiments of the invention are different but need not be mutually exclusive. For example, specific shapes, structures, and characteristics described herein with respect to one embodiment may be implemented in other embodiments without departing from the spirit and scope of the invention. It should also be understood that the location or arrangement of individual components within each disclosed embodiment may be changed without departing from the spirit and scope of the invention. Accordingly, the following detailed description is not intended to be limiting, and the scope of the invention is limited only by the appended claims, including all equivalents to those claimed therein, provided appropriately described. Similar reference numerals in the drawings refer to the same or similar functions across various aspects.

[0044] Hereinafter, preferred embodiments of the present invention will be described in more detail with reference to the drawings.

[0046] The present invention relates to upconversion nanoparticles having a core / shell / shell / shell / shell (core / quadruple shell) structure capable of color control. These nanoparticles are composed of a fluoride-based nanoparticle core with a specific chemical composition and a multilayer shell, and are designed to enable light emission of various colors. In particular, specific rare earth ions contained in the core and shell layers absorb infrared light of different wavelengths and emit visible light, thereby exhibiting light of various colors and realizing color-controllable luminescence characteristics.

[0047] The upconversion nanoparticles of the present invention are composed of a multilayer structure, and each layer is doped with rare earth ions. The rare earth ions doped in each layer selectively absorb infrared radiation of different wavelengths and receive energy to re-emit, so that each layer has unique luminescence characteristics. For example, Yb 3+ , Tm 3+ , Er 3+ , Nd 3+ Rare earth ions such as these can generate various color combinations of blue, red, and green through selective absorption and emission characteristics for different wavelengths.

[0048] The nanoparticle structure of the present invention can be represented by Chemical Formula 1, which consists of fluoride-based layers, each layer composed of different chemical compositions and doping concentrations:

[0049] [Chemical Formula 1]

[0050] NaGd 1-a-b-c L c F4:Yb 3+ a ,Tm 3+ b / NaY 1-d M d F4 / NaEr 1-e-f-g Q e F4:Yb 3+ f ,Tm 3+g / NaY 1-h-i R h F4:Yb 3+ i / NaNd 1-j-k T j F4:Yb 3+ k

[0052] Here, a is a real number such that 0 < a ≤ 1, b is a real number such that 0 < b ≤ 0.5, c is a real number such that 0 ≤ c ≤ 1, and c can be selected within the range satisfying the condition 0 < a + b + c ≤ 1; L is any one selected from the group consisting of rare earth elements and combinations thereof, where L is any one selected from the group consisting of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Tb, Dy, Ho, Er, and Lu; d is a real number such that 0 ≤ d ≤ 1; M is any one selected from the group consisting of rare earth elements and combinations thereof, where M is any one selected from the group consisting of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; e is a real number such that 0 ≤ e < 1, and f is 0 ≤ f < It is a real number of 1, and g is 0 ≤ g ≤ 0.5 is a real number, e can be selected within the range satisfying the condition 0 ≤ e + f + g < 1, Q is any one selected from the group consisting of rare earth elements and combinations thereof, where the rare earth element in Q is any one selected from the group consisting of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, and Lu, h is a real number 0 ≤ h ≤ 1, i is a real number 0 ≤ i ≤ 1, where h is any one selected within the range satisfying 0 ≤ h + i ≤ 1, R is any one selected from the group consisting of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Lu, and combinations thereof, j is a real number 0 ≤ j < 1, k is a real number 0 ≤ k < 1, where j can be selected within the range satisfying the condition 0 ≤ j + k < 1 There is, and T is any one selected from the group consisting of rare earth elements and combinations thereof, and in T, the rare earth element is any one selected from the group consisting of Y, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, and Lu.

[0053] The nanoparticles configured in this way can emit visible light of various colors through the chemical composition of each layer and rare earth ion doping, and are innovative nanoparticles with multiple emission capabilities by absorbing infrared light of a desired wavelength to achieve selective luminescence.

[0054] Hereinafter, the upconversion nanoparticles of the present invention will be described.

[0055] Referring to FIG. 1, the upconversion nanoparticle (10) according to the present invention has a core / shell / shell / shell / shell (core / quadruple shell) structure in which a core (100), an intermediate layer (300) around the core, a light-emitting layer (500), an energy transfer layer (700), and an absorption layer (900) are stacked in order.

[0056] This structure is designed so that each layer performs the function of absorbing or emitting infrared rays of a specific wavelength, thereby efficiently emitting light of the desired wavelength.

[0057] The core (100) has the characteristic of absorbing infrared light corresponding to the first wavelength and emitting blue light, and the intermediate layer (300) surrounds the surface of the core and is formed in a crystalline structure to block energy transfer between the core and the light-emitting layer. The light-emitting layer (500) has a dual light-emitting characteristic of absorbing infrared light of the second wavelength and emitting red light, and emitting green light through infrared light of the third wavelength that is absorbed or received. The energy transfer layer (700) is located around the light-emitting layer (500) and optimizes the overall energy flow by transferring the infrared energy of the third wavelength absorbed by the absorption layer (900) to the light-emitting layer (500). The absorption layer (900) efficiently absorbs infrared light of the third wavelength and enables it to be transferred to the light-emitting layer (500) through the energy transfer layer (700).

[0058] In one embodiment of the present invention, the first wavelength absorbed by the core (100) is infrared radiation of 980 ± 50 nm, preferably set to 980 ± 20 nm, more preferably 980 nm. The second wavelength absorbed by the light-emitting layer (500) is infrared radiation of 1532 ± 50 nm, preferably set to 1532 ± 20 nm, more preferably 1532 nm. Additionally, the third wavelength absorbed by the absorption layer (900) and transmitted to the light-emitting layer (500) is infrared radiation of 800 ± 50 nm, preferably set to 800 ± 20 nm, more preferably 800 nm.

[0059] This structure and the functional arrangement of each layer perform a complex function of absorbing infrared rays of specific wavelengths and emitting various visible lights, and each layer is configured to organically transfer energy to one another and realize optimal light emission characteristics.

[0060] Specific embodiments of a method for manufacturing upconversion multicolor luminescent fluoride-based nanoparticles with a core / shell / shell / shell / shell structure according to the concept of the present invention are described below.

[0062] <Example 1> 0.74 mmol Yb 3+ , 0.01 mmol Tm 3+ Manufacture of revived upconversion core nanoparticles

[0063] 0.25 mmol of dolinium chloride hydrate (GdCl3·6H2O), 0.74 mmol of ytterbium chloride hydrate (YbCl3·6H2O), and 0.01 mmol of thulium chloride hydrate (TmCl3·6H2O) were mixed with a solution containing oleic acid and 1-octadicene and heat-treated at 150°C for 30 minutes to prepare a mixed solution containing a lanthanide complex (first mixed solution preparation step).

[0064] After preparing a 10 ml methanol solution containing 2.5 mmol of sodium hydroxide (NaOH) and 4 mmol of ammonium fluoride (NH4F) in the first mixed solution (second mixed solution preparation step), it was mixed into a mixed solution containing a lanthanide complex (reaction solution preparation step).

[0065] After sufficient mixing, methanol was removed, and heat treatment was performed in an inert gas atmosphere. If the heat treatment temperature is below 200°C, single hexagonal nanocrystals are not completely formed, which prevents the phosphor from exhibiting strong luminescence. If the temperature exceeds 370°C, particle aggregation occurs due to over-reaction, resulting in very large particle sizes and uneven size distribution, which leads to a decrease in brightness. Therefore, it is desirable to set the heat treatment temperature to 200–370°C and the heat treatment time to 10 minutes–4 hours (nanoparticle formation step). After completing the heat treatment process and cooling to room temperature, colloidal nanoparticles with a diameter of 1–30 nm are obtained. The nanoparticles produced in this way were washed with acetone or ethanol and then dispersed in nonpolar solvents such as hexane, toluene, and chloroform for storage.

[0066] Figure 2 shows a transmission electron microscope image of the core upconversion nanoparticles synthesized in Example 1 according to the present invention, and it was confirmed that core nanoparticles having a uniform size of about 24 nm were synthesized.

[0067] Specifically, a transmission electron microscope image of the core of Example 1, which absorbs infrared light of a wavelength of 980 nm and emits blue light, confirms that the core nanoparticles are uniform with a size of approximately 24.2 ± 0.5 nm.

[0069] <Example 2> Preparation of Core / Shell Structured Upconversion Nanoparticles

[0070] NaGdF4:Yb prepared in Example 1 above 3+ 0.74 ,Tm 3+ 0.01 Nanoparticles with a core / shell structure containing a fluoride-based compound were prepared using nanoparticles as the core.

[0071] 1.5 mmol of yttrium chloride hydrate (YCl3·6H2O) was mixed with a solution containing oleic acid and 1-octadicene, and heat-treated at 150°C for 30 minutes to prepare a mixed solution containing a lanthanide complex (first mixed solution preparation step).

[0072] NaGdF4:Yb prepared in Example 1 is added to the first mixed solution above. 3+ 0.74 ,Tm 3+ 0.01 A second mixed solution was prepared by mixing a solution containing nanoparticles.

[0073] After preparing a 15 ml methanol solution containing 3.75 mmol of sodium hydroxide (NaOH) and 6 mmol of ammonium fluoride (NH4F) in the above mixed solution (step 3 for preparing the mixed solution), it was mixed into the mixed solution containing the lanthanide complex (step 3 for preparing the reaction solution).

[0074] After sufficient mixing, methanol was removed, and heat treatment was performed in an inert gas atmosphere. If the heat treatment temperature is below 200°C, single hexagonal nanocrystals are not completely formed, which prevents the phosphor from exhibiting strong luminescence. If the temperature exceeds 370°C, particle aggregation occurs due to over-reaction, resulting in very large particle sizes and uneven size distribution, which leads to a decrease in brightness. Therefore, it is desirable to set the heat treatment temperature to 200–370°C and the heat treatment time to 10 minutes–4 hours (nanoparticle formation step). After completing the heat treatment process and cooling to room temperature, colloidal nanoparticles with a diameter of 5–45 nm are obtained. The nanoparticles produced in this way were washed with acetone or ethanol and then dispersed in nonpolar solvents such as hexane, toluene, and chloroform for storage.

[0075] Figure 3 shows a transmission electron microscope image of the core / shell upconversion nanoparticles prepared through Example 2, and it was confirmed that core / shell upconversion nanoparticles with a uniform size of about 43 nm were synthesized.

[0076] Specifically, it can be confirmed that a crystalline shell is formed around the core nanoparticle of Example 1, and as the particle size increases, nanorod-shaped particles are formed with a size of 42.8 ± 1.4 nm in the long axis direction and 30.3 ± 1.1 nm in the short axis direction. In addition, surface defects of the core are reduced due to the formation of the crystalline shell, which can increase the intensity of the blue light emitted from the core.

[0078] <Example 3> Preparation of Core / Shell / Shell Structured Upconversion Nanoparticles

[0079] NaGdF4:Yb prepared in Example 2 above 3+ 0.74 ,Tm 3+ 0.01 NaErF4:Yb using NaYF4 nanoparticles as a core 3+ ,Tm 3+ Nanoparticles with a core / shell / shell structure containing a compound were prepared.

[0080] 0.815 mmol of erbium chloride hydrate (ErCl3·6H2O), 0.18 mmol of ytterbium chloride hydrate (YbCl3·6H2O), and 0.005 mmol of thulium chloride hydrate (TmCl3·6H2O) were mixed with a solution containing oleic acid and 1-octadicene and heat-treated at 150°C for 30 minutes to prepare a mixed solution containing a lanthanide complex (first mixed solution preparation step).

[0081] NaGdF4:Yb prepared in Example 2 was added to the first mixed solution above. 3+ 0.74 ,Tm 3+ 0.01 A second mixed solution was prepared by mixing a solution containing NaYF4 nanoparticles.

[0082] After preparing a 10 ml methanol solution containing 2.5 mmol of sodium hydroxide (NaOH) and 4 mmol of ammonium fluoride (NH4F) in the above mixed solution (step 3 for preparing the mixed solution), it was mixed into a mixed solution containing a lanthanide complex (step 3 for preparing the reaction solution).

[0083] After sufficient mixing, methanol was removed, and heat treatment was performed in an inert gas atmosphere. If the heat treatment temperature is below 200°C, single hexagonal nanocrystals are not completely formed, which prevents the phosphor from exhibiting strong luminescence. If the temperature exceeds 370°C, particle aggregation occurs due to over-reaction, resulting in very large particle sizes and uneven size distribution, which leads to a decrease in brightness. Therefore, it is desirable to set the heat treatment temperature to 200–370°C and the heat treatment time to 10 minutes–4 hours (nanoparticle formation step). After completing the heat treatment process and cooling to room temperature, colloidal nanoparticles with a diameter of 5–50 nm are obtained. The nanoparticles produced in this way were washed with acetone or ethanol and then dispersed in nonpolar solvents such as hexane, toluene, and chloroform for storage.

[0084] Figure 4 shows a transmission electron microscope image of the core / shell / shell structured upconversion nanoparticles synthesized in Example 3 according to the present invention. Through the transmission electron microscope image, it can be confirmed that the particle size increased further as a shell was formed around the core / shell.

[0085] Specifically, Figure 4 is a transmission electron microscope image of the up-conversion nanoparticles of the core / shell / shell structure of Example 3, in which a light-emitting layer capable of emitting red / green light is formed around the core / shell, and the particle size is increased, showing a size of 48.6 ± 1.3 nm in the long axis direction and 34.5 ± 1.2 nm in the short axis direction.

[0087] <Example 4> Preparation of Up-conversion Core Nanoparticles with Core / Shell / Shell / Shell Structure

[0088] NaGdF4:Yb prepared in Example 3 above 3+ ,Tm 3+ / NaYF4 / NaErF4:Yb 3+ ,Tm 3+ NaYF4:Yb with nanoparticles as the core 3+ Nanoparticles with a core / shell / shell / shell structure containing a compound were prepared.

[0089] 1.8 mmol of yttrium chloride hydrate (YCl3·6H2O) and 0.2 mmol of ytterbium chloride hydrate (YbCl3·6H2O) were mixed with a solution containing oleic acid and 1-octadicene and heat-treated at 150°C for 30 minutes to prepare a mixed solution containing a lanthanide complex (first mixed solution preparation step).

[0090] NaGdF4:Yb prepared in Example 3 was added to the first mixed solution above. 3+ ,Tm 3+ / NaYF4 / NaErF4:Yb 3+ ,Tm 3+ A second mixed solution was prepared by mixing a solution containing nanoparticles.

[0091] After preparing a 20 ml methanol solution containing 5.0 mmol of sodium hydroxide (NaOH) and 8 mmol of ammonium fluoride (NH4F) in the above mixed solution (step 3 for preparing the mixed solution), it was mixed into a mixed solution containing a lanthanide complex (step 3 for preparing the reaction solution).

[0092] After sufficient mixing, methanol was removed, and heat treatment was performed in an inert gas atmosphere. If the heat treatment temperature is below 200°C, single hexagonal nanocrystals are not completely formed, which prevents the phosphor from exhibiting strong luminescence. If the temperature exceeds 370°C, particle aggregation occurs due to over-reaction, resulting in very large particle sizes and uneven size distribution, which leads to a decrease in brightness. Therefore, it is desirable to set the heat treatment temperature to 200–370°C and the heat treatment time to 10 minutes–4 hours (nanoparticle formation step). After completing the heat treatment process and cooling to room temperature, colloidal nanoparticles with a diameter of 7–65 nm are obtained. The nanoparticles thus produced were washed with acetone or ethanol and then dispersed in nonpolar solvents such as hexane, toluene, and chloroform for storage.

[0093] Figure 5 shows a transmission electron microscope image of the core / shell / shell / shell structure upconversion nanoparticles synthesized in Example 4 according to the present invention. Through the transmission electron microscope image, it can be confirmed that the particle size increased further as a shell was formed around the core / shell / shell.

[0094] Specifically, FIG. 5 is a transmission electron microscope image of the up-conversion nanoparticles of the core / shell / shell / shell structure of Example 4, in which a crystalline shell, which is an energy transfer layer, is formed around the core / shell / shell, and the particle size is increased, exhibiting a size of 63.7 ± 1.7 nm in the long axis direction and 39.4 ± 1.3 nm in the short axis direction. The energy transfer layer can increase the luminescence intensity from the emissive layer by reducing surface defects in the second shell, which is the emissive layer.

[0096] <Example 5> Preparation of upconversion nanoparticles with core / shell / shell / shell / shell structure

[0097] NaGdF4:Yb prepared in Example 4 above 3+ ,Tm 3+ / NaYF4 / NaErF4:Yb3+ ,Tm 3+ / NaYF4:Yb 3+ NaNdF4:Yb with nanoparticles as the core 3+ Nanoparticles with a core / shell / shell / shell / shell structure containing a compound were prepared.

[0098] 1.26 mmol of neodymium chloride hydrate (NdCl3·6H2O) and 0.14 mmol of ytterbium chloride hydrate (YbCl3·6H2O) were mixed with a solution containing oleic acid and 1-octadicene and heat-treated at 150°C for 30 minutes to prepare a mixed solution containing a lanthanide complex (first mixed solution preparation step).

[0099] NaGdF4:Yb prepared in Example 4 was added to the first mixed solution above. 3+ ,Tm 3+ / NaYF4 / NaErF4:Yb 3+ ,Tm 3+ / NaYF4:Yb 3+ A second mixed solution was prepared by mixing a solution containing nanoparticles.

[0100] After preparing a 14 ml methanol solution containing 3.5 mmol of sodium hydroxide (NaOH) and 5.6 mmol of ammonium fluoride (NH4F) in the above mixed solution (step 3 of preparing the mixed solution), it was mixed into a mixed solution containing a lanthanide complex (step of preparing the reaction solution).

[0101] After sufficient mixing, methanol was removed, and heat treatment was performed in an inert gas atmosphere. If the heat treatment temperature is below 200°C, single hexagonal nanocrystals are not completely formed, which prevents the phosphor from exhibiting strong luminescence. If the temperature exceeds 370°C, particle aggregation occurs due to over-reaction, resulting in very large particle sizes and uneven size distribution, which leads to a decrease in brightness. Therefore, it is desirable to set the heat treatment temperature to 200–370°C and the heat treatment time to 10 minutes–4 hours (nanoparticle formation step). After completing the heat treatment process and cooling to room temperature, colloidal nanoparticles with a diameter of 10–90 nm are obtained. The nanoparticles produced in this way were washed with acetone or ethanol and then dispersed in nonpolar solvents such as hexane, toluene, and chloroform for storage.

[0102] Figure 6 shows a transmission electron microscope image of the core / shell / shell / shell / shell structure upconversion nanoparticles synthesized in Example 5 according to the present invention. Through the transmission electron microscope image, it can be confirmed that the particle size increased further as a shell was formed around the core / shell / shell.

[0103] Specifically, Figure 6 is a transmission electron microscope image of the upconversion nanoparticles of the core / shell / shell / shell / shell structure of Example 5, in which an 800 nm infrared absorption layer is formed around the core / shell / shell / shell, increasing the particle size to 89.3 ± 2.6 nm and 41.2 ± 1.9 nm in the short axis direction. It can be confirmed that dumbbell-shaped particles of uniform size are formed when the final shell is formed. When the nanoparticles are excited by 800 nm infrared light, the energy absorbed in the absorption layer moves through the energy transfer layer to the emission layer, and then green light emission occurs.

[0105] According to the X-ray diffraction pattern shown in Fig. 7, it can be seen that the upconversion nanoparticles of the core, core / shell, core / shell / shell, core / shell / shell, and core / shell / shell / shell structures synthesized through Examples 1 to 5 exhibit a hexagonal single phase free of impurities.

[0106] FIG. 8 shows the emission spectrum when the core / shell / shell / shell / shell upconversion nanoparticles according to Example 5 of the present invention are excited by 980 nm infrared light. A strong emission peak appears from the core in the 450 to 480 nm spectral region, and the core / shell / shell / shell / shell upconversion nanoparticles exhibit blue emission.

[0107] FIG. 9 shows the emission spectrum when the core / shell / shell / shell / shell upconversion nanoparticles according to Example 5 of the present invention are excited by 800 nm infrared radiation. Under 800 nm infrared excitation conditions, when the outermost absorption layer absorbs 800 nm infrared radiation, it is transferred to the activator of the second shell through the energy transfer layer, which is the third shell. Through this, a strong emission peak appears from the second shell in the 500–560 nm spectral region, and the core / shell / shell / shell / shell upconversion nanoparticles exhibit green emission.

[0108] FIG. 10 shows the emission spectrum when the core / shell / shell / shell / shell upconversion nanoparticles according to Example 5 of the present invention are excited by 1532 nm infrared light. Under 1532 nm infrared excitation conditions, the activator doped in the second shell absorbs 1532 nm near-infrared light and then exhibits an emission peak in the 650 to 700 nm spectral region, so the core / shell / shell / shell / shell upconversion nanoparticles exhibit red emission.

[0109] Figure 11 shows a luminescence photograph of a core / shell / shell / shell / shell upconversion nanoparticle solution according to Example 5 of the present invention. It can be seen that blue, green, and red luminescence are observed when excited by infrared rays at 980 nm, 800 nm, and 1532 nm from the left.

[0110] From the emission spectra shown in FIGS. 8 to 10 and the emission photograph shown in FIG. 11, it can be seen that the core / shell / shell / shell / shell upconversion nanoparticles synthesized in Example 5 exhibit green emission under 800 nm near-infrared excitation, blue emission under 980 nm near-infrared excitation, and red emission under 1532 nm near-infrared excitation.

[0112] FIG. 12 is a color coordinate under conditions in which upconversion nanoparticles of a core / shell / shell / shell / shell (core / quadruple shell) structure according to preferred embodiment 5 of the present invention are excited by infrared rays of various wavelengths.

[0113] Referring to FIG. 12, it can be seen that various emission colors, such as blue, sky blue, cyan, green, light green, yellow, orange, red, purple, and violet, can be realized depending on the combination of wavelengths of infrared light applied to the core / quadruple-shell upconversion nanoparticles. It can be seen that the color reproduction range achievable from the blue, green, and red emission from the core / quadruple-shell upconversion nanoparticles of the present invention represents a very wide color reproduction range, which is 128% of the sRGB range used as the standard for HD TVs.

[0115] <Example 6> Preparation of a polymer composite containing red / green / blue luminescent upconversion nanoparticles with a core / shell / shell / shell / shell structure

[0116] NaGdF4:Yb prepared in Example 5 above 3+ ,Tm 3+ / NaYF4 / NaErF4:Yb 3+ ,Tm 3+ / NaYF4:Yb 3+ / NaNdF4:Yb 3+ A polymer composite was prepared by mixing nanoparticles with a core / shell / shell / shell / shell structure with a polydimethyl siloxane (PDMS) polymer.

[0117] A polymer composite was prepared by mixing 0.4 ml of a core / shell / shell / shell / shell structured nanoparticle solution prepared in Example 6 with 10 ml of Sylgard 184 PDMS polymer and 1 ml of curing agent, and then heat-treating at 80°C for 1 hour.

[0118] Figure 13 shows a photograph of the core / shell / shell / shell / shell structured upconversion nanoparticle-polymer composite prepared in Example 6 according to the present invention, and it can be seen that a composite was prepared that is transparent enough to show the text in the background behind the upconversion nanoparticle-polymer composite.

[0119] In addition, FIG. 14 shows a luminescence photograph when an infrared laser is applied to a core / quadruple-shell upconversion nanoparticle-polymer composite according to Example 6 of the present invention.

[0120] FIG. 14(a) is a photograph showing that a blue circle can be displayed when a 980 nm infrared laser is applied to a core / quadruple-shell upconversion nanoparticle-polymer composite according to Example 6 of the present invention.

[0121] FIG. 14(b) is a photograph showing that a green circle can be displayed when an 800 nm infrared laser is applied to a core / quadruple-shell upconversion nanoparticle-polymer composite according to Example 6 of the present invention.

[0122] FIG. 14(c) is a photograph showing that a red circle can be displayed when a 1532 nm infrared laser is applied to a core / quadruple-shell upconversion nanoparticle-polymer composite according to Example 6 of the present invention.

[0123] FIG. 14(d) is a photograph showing that blue, green, and red circles can be displayed simultaneously when 980 nm, 800 nm, and 1532 nm infrared rays are simultaneously irradiated onto a core / quadruple-shell upconversion nanoparticle-polymer composite according to Example 6 of the present invention.

[0124] Accordingly, it was found that, similar to the core / shell / shell / shell / shell structured upconversion nanoparticles, the nanoparticle-polymer composite also exhibits green emission under 800 nm near-infrared excitation, blue emission under 980 nm near-infrared excitation, and red emission under 1532 nm near-infrared excitation. In addition, it was confirmed that when all three wavelengths of near-infrared light were applied to the polymer composite, red, green, and blue emission could be displayed from a single upconversion nanoparticle-polymer composite.

[0125] Although the invention has been described above with reference to embodiments, those skilled in the art will understand that various modifications and changes can be made to the invention without departing from the spirit and scope of the invention as described in the following claims. Industrial applicability

[0127] By dispersing the core / quadruple-shell nanoparticles of the present invention in a polymer medium to fabricate a transparent polymer composite, a high-resolution 3D display without viewing angle limitations can be realized. Through this, users can experience immersive 3D images, and the core / quadruple-shell nanoparticles of the present invention and the polymer composite containing them can be applied to next-generation display technologies such as virtual reality (VR), augmented reality (AR), and hologram technology.

[0128] Furthermore, the upconversion nanoparticle-polymer composite of the present invention can be applied to various industrial fields, including transparent displays, volumetric displays, electronic displays, and anti-counterfeiting, as well as medical, advertising, design, simulation, education, and training. In particular, visual effects can be maximized in various industries through the realization of full color with strong luminescence performance and high color reproduction.

[0129] Furthermore, by simplifying complex processes, it is possible to reduce energy and resource waste that may occur during the manufacturing process, making it applicable as an eco-friendly manufacturing technology.

Claims

Claim 1 An upconversion nanoparticle having a core / quadruple-shell structure represented by the following chemical formula 1, comprising: a core that absorbs infrared radiation of a first wavelength and emits blue light; a crystalline intermediate layer formed around the core; a single-layer emitting layer formed around the intermediate layer that absorbs infrared radiation of a second wavelength and emits red light, and emits green light by infrared radiation of a third wavelength absorbed from the absorption layer and transmitted through an energy transmission layer; an energy transmission layer formed around the emitting layer and transmitting absorbed infrared radiation of a third wavelength to the emitting layer; and an absorption layer formed around the energy transmission layer that absorbs infrared radiation of a third wavelength and transmits it to the emitting layer through the energy transmission layer; wherein [Chemical Formula 1]NaGd 1-a-b-c L c F4:Yb 3+ a ,Tm 3+ b / NaY 1-d M d F4 / NaEr 1-e-f-g Q e F4:Yb 3+ f ,Tm 3+ g / NaY 1-h-i R h F4:Yb 3+ i / NaNd 1-j-k T j F4:Yb 3+ k Here, a is a real number such that 0 < a ≤ 1, b is a real number such that 0 < b ≤ 0.5, c is a real number such that 0 ≤ c ≤ 1, and c can be selected within the range satisfying the condition 0 < a + b + c ≤ 1, d is a real number such that 0 ≤ d ≤ 1, e is a real number such that 0 ≤ e < 1, f is a real number such that 0 ≤ f < 1, g is a real number such that 0 ≤ g ≤ 0.5, and e can be selected within the range satisfying the condition 0 ≤ e + f + g < 1, h is a real number such that 0 ≤ h ≤ 1, i is a real number such that 0 ≤ i ≤ 1, where h is any one selected within the range satisfying 0 ≤ h + i ≤ 1, j is a real number such that 0 ≤ j < 1, and k is a real number such that 0 ≤ k < 1, where j is 0 Upconversion nanoparticles that can be selected within a range satisfying the condition ≤ j + k < 1, where L, M, Q, R, and T are any one selected from the group consisting of rare earth elements and combinations thereof. Claim 2 In claim 1, L is any one selected from the group consisting of rare earth elements and combinations thereof, and the rare earth element in L is any one selected from the group consisting of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Tb, Dy, Ho, Er, and Lu; M is any one selected from the group consisting of rare earth elements and combinations thereof, and the rare earth element in M ​​is any one selected from the group consisting of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; Q is any one selected from the group consisting of rare earth elements and combinations thereof, and the rare earth element in Q is any one selected from the group consisting of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, and Lu; and R is any one selected from the group consisting of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Lu, and combinations thereof An upconversion nanoparticle, wherein T is any one selected from the group consisting of rare earth elements and combinations thereof, and in T, the rare earth element is any one selected from the group consisting of Y, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm and Lu. Claim 3 Upconversion nanoparticles according to claim 1, wherein the first wavelength is 980 ± 50 nm, the second wavelength is 1532 ± 50 nm, and the third wavelength is 800 ± 50 nm. Claim 4 Upconversion nanoparticles having a single hexagonal crystal phase in claim 1. Claim 5 Upconversion nanoparticles according to claim 1, emitting white or various colors depending on the relative intensity of applied 980 ± 50 nm, 800 ± 50 nm, and 1532 ± 50 nm near-infrared rays. Claim 6 A polymer composite comprising the upconversion nanoparticles according to any one of claims 1 to 5. Claim 7 A display device applying the up-conversion nanoparticles according to any one of claims 1 to 5. Claim 8 NaGd 1-a-b-c L c F4:Yb 3+ a ,Tm 3+ b A step of forming a nano-sized core represented by the chemical formula; NaY around the core 1-d M d A step of forming a first shell represented by the chemical formula of F4; NaEr around the first shell 1-e-f-g Q e F4:Yb 3+ f ,Tm 3+ g A step of forming a second shell as a single light-emitting layer represented by the chemical formula, which directly absorbs infrared rays of a second wavelength to emit red light and emits green light through energy transfer; NaY around the second shell 1-h-i R h F4:Yb 3+ i A step of forming a third shell represented by the chemical formula of; and NaNd around the third shell 1-j-k T j F4:Yb 3+ k The method comprises the step of forming a fourth shell represented by the chemical formula of; wherein a is a real number of 0 < a ≤ 1, b is a real number of 0 < b ≤ 0.5, c is a real number of 0 ≤ c ≤ 1, c can be selected within the range satisfying the condition 0 < a + b + c ≤ 1, d is a real number of 0 ≤ d ≤ 1, e is a real number of 0 ≤ e < 1, f is a real number of 0 ≤ f < 1, g is a real number of 0 ≤ g ≤ 0.5, e can be selected within the range satisfying the condition 0 ≤ e + f + g < 1, h is a real number of 0 ≤ h ≤ 1, i is a real number of 0 ≤ i ≤ 1, wherein h is any one selected within the range satisfying 0 ≤ h + i ≤ 1, j is a real number of 0 ≤ j < 1, and k is A method for manufacturing upconversion nanoparticles, wherein 0 ≤ k < 1 is a real number, where j can be selected within a range satisfying the condition 0 ≤ j + k < 1, and L, M, Q, R, and T are any one selected from the group consisting of rare earth elements and combinations thereof. Claim 9 In paragraph 8, L is any one selected from the group consisting of rare earth elements and combinations thereof, where L is any one selected from the group consisting of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Tb, Dy, Ho, Er, and Lu; M is any one selected from the group consisting of rare earth elements and combinations thereof, where M is any one selected from the group consisting of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; Q is any one selected from the group consisting of rare earth elements and combinations thereof, where Q is any one selected from the group consisting of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, and Lu; and R is any one selected from the group consisting of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Lu, and combinations thereof A method for preparing upconversion nanoparticles, wherein T is one selected from the group consisting of rare earth elements and combinations thereof, and the rare earth element in T is any one selected from the group consisting of Y, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, and Lu. Claim 10 A method for manufacturing upconversion nanoparticles according to claim 8, wherein the core absorbs infrared rays of a first wavelength and emits blue light, the second shell absorbs infrared rays of a second wavelength and emits red light, and emits green light through infrared rays of a third wavelength absorbed from the fourth shell and transmitted through the third shell. Claim 11 A method for manufacturing upconversion nanoparticles according to claim 8, wherein the first wavelength is 980 ± 50 nm, the second wavelength is 1532 ± 50 nm, and the third wavelength is 800 ± 50 nm. Claim 12 A method for manufacturing upconversion nanoparticles according to claim 8, wherein the step of forming a core comprises: a step of preparing a first lanthanide complex using dolinium chloride hydrate (GdCl3·6H2O), ytterbium chloride hydrate (YbCl3·6H2O), and thulium chloride hydrate (TmCl3·6H2O); a step of preparing a first methanol solution containing sodium hydroxide (NaOH) and ammonium fluoride (NH4F); and a step of preparing a nanoparticle solution having a core structure by mixing the first methanol solution and the first lanthanide complex. Claim 13 A method for manufacturing upconverted nanoparticles according to claim 12, wherein the step of forming the first shell comprises: a step of preparing a second lanthanide complex using yttrium chloride hydrate (YCl3·6H2O); a step of preparing a first mixed solution by mixing the second lanthanide complex and a core-structured nanoparticle solution; a step of preparing a second methanol solution containing sodium hydroxide (NaOH) and ammonium fluoride (NH4F); and a step of preparing a core / shell structured nanoparticle solution by mixing the second methanol solution and the first mixed solution. Claim 14 A method for manufacturing upconverted nanoparticles according to claim 13, wherein the step of forming a second shell comprises: a step of preparing a third lanthanide complex using erbium chloride hydrate (ErCl3·6H2O), ytterbium chloride hydrate (YbCl3·6H2O), and thulium chloride hydrate (TmCl3·6H2O); a step of preparing a second mixed solution by mixing the third lanthanide complex and a core / shell structured nanoparticle solution; a step of preparing a third methanol solution containing sodium hydroxide (NaOH) and ammonium fluoride (NH4F); and a step of preparing a core / shell / shell structured nanoparticle solution by mixing the third methanol solution and the second mixed solution. Claim 15 A method for manufacturing upconverted nanoparticles according to claim 14, wherein the step of forming the third shell comprises: a step of preparing a fourth lanthanide complex using yttrium chloride hydrate (YCl3·6H2O) and ytterbium chloride hydrate (YbCl3·6H2O); a step of preparing a third mixed solution by mixing the fourth lanthanide complex with a core / shell / shell structured nanoparticle solution; a step of preparing a fourth methanol solution containing sodium hydroxide (NaOH) and ammonium fluoride (NH4F); and a step of preparing a core / shell / shell / shell structured nanoparticle solution by mixing the fourth methanol solution and the third mixed solution. Claim 16 A method for manufacturing upconverted nanoparticles according to claim 15, wherein the step of forming the fourth shell comprises: a step of preparing a fifth lanthanide complex using neodymium chloride hydrate (NdCl3·6H2O) and ytterbium chloride hydrate (YbCl3·6H2O); a step of preparing a fourth mixed solution by mixing the fifth lanthanide complex with a nanoparticle solution having a core / shell / shell / shell structure; a step of preparing a fifth methanol solution containing sodium hydroxide (NaOH) and ammonium fluoride (NH4F); and a step of preparing a nanoparticle solution having a core / shell / shell / shell / shell structure by mixing the fifth methanol solution and the fourth mixed solution. Claim 17 A method for manufacturing upconversion nanoparticles according to claim 8, wherein each step comprises a step of heat treating at a temperature of 200°C to 370°C for 10 minutes to 4 hours in an inert gas atmosphere.

Citation Information

Patent Citations

  • Full color tunable upconversion nanophosphor

    KR1020220027648A

  • Upconversion multi-color-emitting polymer composite, transparent display including the same and method for manufacturing the same

    KR1020240048967A

  • Rare earth nano composite material capable of improving generation of singlet oxygen as well as preparation method and application of rare earth nano composite material

    CN114836216A

  • Multi-color tunable upconversion nanophosphor

    KR1020230011711A